(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
A continuous washing experiment was carried out using water types with different ionic strengths, as the electrical conductivity of river water is 2.05 siemens M-1 and the tap water is 5.71 siemens M-1W. And two sites in Al-Kifl (and each site has two depths) (0-20 and (20-40) cm to know the speed of salt movement collectively depending on the time factor. The statistical program Statistical was used to know the effect of water of different ionic strengths on the content of soils of different salinities and textures. the results of the continuous washing experiment using two types of water of different ionic strengths show that the highest concentration of liberated chloride was accumulated in the sample of the Kifl site (second site) Ct2 A G2 amounting to 98.152 centimos kg-1 treated with tap water and the lowest concentration was in the Mouradian site of 9.835 centimos kg 1- Treatment with river water. The kinetic equations (force function equation, diffusion equation) were applied to describe the kinetic behavior of chloride ion liberation from the soil using the Statistical program.